Oral yohimbine as a new probe drug to predict CYP2D6 activity: results of a fixed-sequence phase I trial - Vay, Manuela; Meyer, Marleen J.; Blank, Antje; Skopp, Gisela; Rose, Peter; Tzvetkov, Mladen Vassilev; Mikus, Gerd (Clinical pharmacokinetics, 2020)
Yohimbine pharmacokinetics were determined after oral administration of a single oral dose of yohimbine 5 mg and a microdose of yohimbine 50 µg in relation to different cytochrome P450 (CYP) 2D6 genotypes. The CYP2D6 inhibitor paroxetine was used to investigate the influence on yohimbine pharmacokinetics. Microdosed midazolam was applied to evaluate a possible impact of yohimbine on CYP3A activity and the possibility of combining microdosed yohimbine and midazolam to simultaneously determine CYP2D6 and CYP3A activity.